Efektivitas Model Pembelajaran Think-Talk-Write dalam Meningkatkan Komunikasi Matematis Mahasiswa Pendidikan Matematika - Siska Candra Ningsih (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
This research has aims to determine the effectiveness of learning model Think-Talk-Write (TTW) and determine whether the learning TTW modelis more effective than conventional learning to improve student mathematical communication. The research is a quasi experimental research. The populationin this research were all students ofthe second semester in Mathematics Education department. They are divided into four parallel classes. Samples were IIA2 class as the control class and the IIA1 class as a class experiment in Number Theory lesson. The instrument in this researcsh was test of mathematical communication. The analysies of data use SPSS 16, the proportion test of one population, and t test. The hypotesis tests use the proportion test of one population and t test. Based on the results of this research were concluded that : (1) The mathematical learning by learning model Think-Talk-Write is effective to improve the mathematical communication students. It can be proved fromthe results of proportion testonan experimental class of mathematical communication valueis 1.87 > z table with a significance level 5%. Z table is 1.64. (2)The learning model Think-Talk-Write more effective than conventional approaches. It can be proved from the results of t test. The value of mathematical communicationis 2.07 >t table with a significance level 5%. t table is 1.67.